The 5 essential people skills how to assert yourself, listen to others, and resolve conflicts - Carnegie, Dale. (New York Simon & Schuster, 2009)
The 5 Essential people skills will help you be the most positively commanding, prosperous and inspired professional you can be. you will learn to
Keywords: Interpersonal relations